Single-cell and machine learning integration reveals OS-driven CCND1 promotes an aggressive phenotype in papillary thyroid carcinoma - Wang, Jiaxi; Zhu, Qingyi; Bie, Jingyi; Han, Yueyu; Liu, Hanqing; Chen, Chuang (Frontiers in Immunology, 2026)
BackgroundPapillary thyroid carcinoma (PTC) is the most common thyroid malignancy, with rising incidence worldwide. Oxidative stress (OS), characterized by an imbalance between reactive oxygen species (ROS) and antioxidant defenses, plays a critical role in tumor initiation and progression. However, the specific relationship between OS and PTC remains underexplored, highlighting the need for further investigation. This study aims to identify OS-related biomarkers in PTC that could potentially be used for clinical diagnosis and treatment.MethodsSingle-cell RNA sequencing data from PTC and normal thyroid tissues were analyzed using multiple gene set scoring and differential expression methods to evaluate OS levels across different cell types. Integrated bioinformatics analysis, including WGCNA and machine learning models, was employed to select candidate biomarkers, which were then validated in independent datasets. Pseudotime analysis and CellChat were conducted to explore cell dynamics within the tumor microenvironment. An oxidative stress model was established in TPC-1 cells using hydrogen peroxide treatment. The levels of OS and changes in tumor cell proliferative capacity were assessed through western blotting, immunoblotting, ROS detection, and cell viability assays.ResultsThe study revealed that CCND1 and SOX4 were highly expressed in PTC, promoting tumor cell proliferation, invasion, and maintaining an undifferentiated state. Both genes were closely linked to OS, which amplified their expression and enhanced tumor growth and immune evasion. CCND1 was particularly involved in M2 macrophage polarization via the PROS1-AXL pathway, while SOX4 regulated angiogenesis through the MDK pathway. In contrast, TFF3 expression was significantly lower in PTC, suggesting a tumor-suppressive role, potentially through modulating immune responses and reducing OS.ConclusionCCND1 is identified as a key oncogene in PTC, whose high expression promotes tumor progression through OS-related pathways like PI3K/AKT and MAPK. Our in vitro findings specifically validate that OS directly drives CCND1 overexpression and subsequent cell proliferation. Conversely, SOX4 also acts as an oncogene, and TFF3 as a potential tumor suppressor, both linked to OS. Targeting CCND1 and its OS-mediated regulatory pathways offers a promising therapeutic strategy for PTC.CCND1, oxidative stress, papillary thyroid carcinoma, single-cell RNA sequencing, SOX4, TFF3.